Model dasar erosi-pengendapan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT A layered cohesive sediment bed model used to simulate the formation, erosion and deposition of the type of beds typically found in estuaries is described. The model is divided into three bed sections